#MeToo and cyber activism in China: gendered violence and scripts of power - Ma, Li (Global gender, 2022)
"This book focusses on the #MeToo movement in China, critically examining how three competing ideologies have worked in co-opting #MeToo activism: China's official communism, Western neoliberalism, and an emerging Chinese cyber-feminism. In 2018, China's #MeToo cyber activism initially maintained its momentum despite strict censorship, presenting women's voices against gendered violence and revealing scripts of power in different sectors of society. Eventually though it lost impetus with sloganization and stigmatization under a trio forces of pressures: corporate corruption, over-politicization by Western media and continued state censorship. The book documents the social events and gendered norms in higher education, NGOs, business and religious circles that preceded and followed high-profile cases of alleged sexual abuses in mainland China, engaging with sociological scholarship relating to demoralization and power, media studies and gender studies. Through these entwined theories the author seeks to give both scholars and the general audience in gender studies a window into the ongoing tension in the power spheres of state, market and gendered hierarchy in contemporary Chinese society. This book will be of interest to students of gender studies, China studies, media studies, and cultural Studies"--